Pelvic X-ray examinations in follow-up of hip arthroplasty or femoral osteosynthesis – Dose reduction and quality criteria. Issue 5 (May 2015) - Kloth, Jost Karsten; Rickert, Markus; Gotterbarm, Tobias; Stiller, Wolfram; Burkholder, Iris; Kauczor, Hans-Ulrich; Ewerbeck, Volker; Weber, Marc-André
Highlights: Pelvic radiographs with speed class 400 and 800 in follow-up of hip arthroplasty were compared. Radiographs with reduced dose (800) were not inferior to those with standard dose (400). We recommend speed class 800 as new reference parameter in these examinations. Abstract: Objective: Digital plain radiographs of the pelvis are frequently performed in follow-up examinations of patients who received total hip arthroplasty (THA) or osteosynthesis (OS). Thus, the purpose was to reduce the radiation dose and to determine objective quality control criteria to ensure accurate assessment. Materials and methods: Institutional review board approval was obtained. In this prospective randomized study, 289 patients underwent X-ray examination of the pelvis as follow up after receiving THA or OS with standard and reduced dose. The evaluation of the plain radiographs was conducted using the following criteria: bone–implant interface, implant–implant discrimination, implant–surface character and periarticular heterotopic ossification. Two radiologists evaluated these criteria using a score ranging from 1 (definitely assessable) to 4 (not assessable). If a single criterion had been evaluated with a score of 3 or more or more than 2 criteria with 2 points, the radiograph was scored as "not assessable". The study was designed as non-inferiority-trial. Results: Seven (2.4%) examined X-rays were scored as not assessable. There was no statistical inferiority between the examinations with standard (0.365 mSv) or reduced dose (0.211 mSv). Reduced dose only led to limitations in the evaluation of ceramic components with low clinical impact in most scenarios. Conclusion: Plain radiography of the pelvis in patients with THA or OS can be performed with a dose reduction of about 42% without a loss of important information. The obtained quality control criteria were clinically applicable.